PLEASE HELP ME ASAP - WILL MARK AS BRAINLIEST - 20 POINTS! THANK YOU!

Find the inverse function for f(x) = 3 - 2x. If it helps, think of it as y = 3 - 2x. Below, you can just think of the f^-1 as y (but this time it's the y value for the inverse function).

A: f^-1(x) = 2(3 - x)

B: f^-1(x) = 3 - x/2

C: f^-1(x) = 3 - 2x

D: f^-1(x) = (3 - x) / 2

E: f^-1(x) = (x - 3) / 2

Respuesta :

Answer:

D: f^-1(x) = (3 - x) / 2

Step-by-step explanation:

To find the inverse of a function, we exchange x and y, then solve for y

y = 3 -2x

Exchange x and y

x = 3 -2y

Subtract 3 from each side

x-3 = -2y

Divide by -2

(x-3)/-2 =y

(3-x)/2 = y

The inverse is 1/2 (3-x)